2018
DOI: 10.1038/s41370-018-0094-1
|View full text |Cite
|
Sign up to set email alerts
|

A review of the pathways of human exposure to poly- and perfluoroalkyl substances (PFASs) and present understanding of health effects

Abstract: Here we review present understanding of sources and trends in human exposure to poly- and perfluoroalkyl substances (PFASs) and epidemiologic evidence for impacts on cancer, immune function, metabolic outcomes, and neurodevelopment. More than 4000 PFASs have been manufactured by humans and hundreds have been detected in environmental samples. Direct exposures due to use in products can be quickly phased out by shifts in chemical production but exposures driven by PFAS accumulation in the ocean and marine food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
970
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,605 publications
(983 citation statements)
references
References 153 publications
10
970
2
1
Order By: Relevance
“…; Sunderland et al. ). Classifying PFAS as hazardous substances would trigger regulation of their manufacture and use.…”
Section: What Are Pfas and Where Are They Found?mentioning
confidence: 98%
See 2 more Smart Citations
“…; Sunderland et al. ). Classifying PFAS as hazardous substances would trigger regulation of their manufacture and use.…”
Section: What Are Pfas and Where Are They Found?mentioning
confidence: 98%
“…Estimates show that 5 million or more Americans have been exposed to these chemicals in their drinking water (USEPA 2019). Secondary sources include wild and farmed meat and crops that have taken up contaminated water, interaction with consumer products that contain PFAS, and background atmospheric deposition (Ahrens and Bundschuh 2014;Sunderland et al 2018). Human exposure through consumption of harvested fish and wildlife is a growing concern (MDN 2018; NJDEP 2018).…”
Section: What Are the Dangers Of Pfas For Human Health And The Aquatimentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, human epidemiological studies have indicated correlations between PFAS exposure and physiological, immunological, and developmental problems (Guelfo et al 2018 ;Sunderland et al 2018 ). An example of developmental effects was presented by Jeddy et al ( 2017 ), where higher concentration of PFAS in maternal serum was associated with lower vocabulary and language skills in children from 15 to 38 months of age.…”
Section: What Are the Dangers Of Pfas For Human Health And The Aquatimentioning
confidence: 99%
“…Estimates show that 5 million or more Americans have been exposed to these chemicals in their drinking water (USEPA 2019 ). Secondary sources include wild and farmed meat and crops that have taken up contaminated water, interaction with consumer products that contain PFAS, and background atmospheric deposition (Ahrens and Bundschuh 2014 ;Sunderland et al 2018 ). Human exposure through consumption of harvested fi sh and wildlife is a growing concern (MDN 2018 ; NJDEP 2018 ).…”
Section: What Are the Dangers Of Pfas For Human Health And The Aquatimentioning
confidence: 99%